2012
DOI: 10.1021/je3005112
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures, Reaction Rates, and Selected Physical Properties of Halo-Boronsubphthalocyanines (Halo = Fluoride, Chloride, and Bromide)

Abstract: The physical properties, including the solid state arrangement, photophysics, solubility, and electrochemical behavior of a series of halo-BsubPcs (halo = F, Cl, Br) have been measured (IUPAC name halo-(7,12:14,19-diimino-21,5-nitrilo-5H-tribenzo(c,h,m)(1,6,11)triazacyclopentadecinato)-boron(III)). We have found that across the series all are relatively similar in most regards. Exceptions include that F-BsubPc can be 5 to 25 times more soluble than Cl-BsubPc in common organic solvents. F-BsubPc was also found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 40 publications
6
88
0
Order By: Relevance
“…The ring system is conical in shape with an apical central boron with an axial ligand, usually a halogen ( X = F, Cl, Br) [4], making these macrocycles more polar and less aggregative than their planar tetrapyrrole phthalocyanine (Pc) cousins. Like Pcs, SPcs are synthesized by the templated cyclization of phthalonitrile derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The ring system is conical in shape with an apical central boron with an axial ligand, usually a halogen ( X = F, Cl, Br) [4], making these macrocycles more polar and less aggregative than their planar tetrapyrrole phthalocyanine (Pc) cousins. Like Pcs, SPcs are synthesized by the templated cyclization of phthalonitrile derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Recently,a no verall efficiency of 4.69 %h as been achieved by using BsubPc chloride (Cl-BsubPc;F igure 1a) as an electron acceptorw hen paired with sexithiophene (a-6T,F igure 1a). [5][6][7][8][9][10][11][12][13][14] For the most part, the derivatives we have synthesized are amenable to vacuum processing and fabricationi nto OPVs by sublimation. [4] Our laboratory has been interested in the synthesis of new BsubPc derivatives for some time now.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Our laboratory has been interested in the synthesis of new BsubPc derivatives for some time now. [5][6][7][8][9][10][11][12][13][14] For the most part, the derivatives we have synthesized are amenable to vacuum processing and fabricationi nto OPVs by sublimation. For ex-ample,w eh ave recently shown that ad erivativeo ther than Cl-BsubPc, pentafluorophenoxy BsubPc( F 5 -BsubPc), can function within ap lanar heterojunction OPV as either an electron-acceptor or electron-donor material.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chloro aluminum Pc (Cl-AlPc) has been paired with C 60 for the fabrication of a planar heterojunction (PHJ) and blended organic photovoltaic (OPV) devices. [11][12][13][14] Moving one level down on the periodic table, and given the successful use of Cl-AlPc in OPV devices [5][6][7][8] we decided to look at the effect of substituting the axial chloride of Cl-AlPc with a fluoride and incorporate fluoro aluminum Pc (F-AlPc) into simple PHJ OPV devices. 10 Our group has recently been studying the incorporation of fluorine groups into boron subphthalocyanine (a sub-class of Pcs) which resulted in a decreases in sublimation temperature, a change in the solid-state arrangement (crystal structure) and a change in electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%